Congenital Heart Disease Characteristics in Low Birth Weight Infants at Dr. Hasan Sadikin General Hospital in 2010–2014 - Villia Damayantie; Sri Endah Rahayuningsih; Irvan Afriandi (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Congenital heart disease (CHD) is a multifactorial disease defined as an anomaly in the macroscopic structure of the heart that may cause functional disorders. The incidence of CHD is reported higher in infants with low birth weight (LBW) than the entire population of neonates. This study aimed to describe the characteristics of CHD in infants born with LBW.Methods: This was a retrospective descriptive study with a cross-sectional design, performed in October–November 2015. Data were obtained from medical records of inpatients infants at Dr. Hasan Sadikin General Hospital, Bandung in the period of 2010–2014. The data presented were the characteristics of CHD in LBW infants.Results: Of 364 LBW infants treated in the hospital within 5 years period, 21 infants (14 girls and 7 boys) were diagnosed as CHD, with birth weight group predominantly (n18; 85.7%) in the range of 1,500–2,499 gr. Non-cyanosis CHD was prevalent in 95.2% (n20),and patent ductus arteriosus (PDA)was found in 76.1% (n16). Comorbid conditions mostly found in this study were preterm birth (n17), sepsis (n10), and neonatal hyperbilirubinemia (n9).Conclusions: The most common type of CHD in low birth weight infants in Dr. Hasan Sadikin General Hospital is Patent Ductus Arteriosus. The presence of congenital heart disease should be considered in low birth weight infants, thus it is essential to perform screening for early recognition.